Keep it simple, silly - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
There are some basic rules in writing. They crop up in every training event: go for clarity, simplicity and brevity. The maximum length of a sentence that should be memorised is 12 words. And, for it to be memorised, write the sentence simply,...